Learn to code with Python 3. (Manning Publications, 2023)
Python is the #1 programming language for beginners due to its simple syntax, wide range of applications, and helpful community resources. This course, intended for absolute beginners, will start you on your coding journey with Python 3, the most recent version of the language. We start by setting up a Python environment and learning programming basics, then move on to cover object-oriented programming, regular expressions, interacting with HTTP (Hypertext Transfer Protocol), networking and more. Enroll now to receive over 17 hours of HD video tutorials with English captions, and a certificate of completion! Python calculator After learning Python basics, we will code our first program, a calculator. Web scraping We will code a simple web scraper to extract data rom a web site. This will demonstrate how to use Python to interact with HTTP. Chat program We will code a chat program using another communication protocol, WebSockets, to learn the basics of networking with Python.